SIGNIFICANCE OF INTEGRATED MARKETING STRATEGY IN EXPANDING UZBEKISTAN'S SHARE IN GLOBAL TOURISM MARKETS - Khudoyarov Anvar Aidjanovich (Journals Park Publishing, 2023)
In this article, in order to ensure the effective operation of the tourism industry in the world economy, the fierce competition in the tourism market in Uzbekistan, suggestions have been developed on the active use of the elements of the integrated marketing strategy in the field.
Keywords: marketing strategy, concept, integration, tourism, pilgrimage tourism, diversification, entrepreneurship, coordination, standard, cooperation, legal and economic norms, international relations.